Partner influences on young women's risky drug and sexual behavior - Miriam Clark; Rohanna Buchanan; Rachel Kovensky; Leslie D. Leve (BMC, 2018)
Abstract Background Adolescent girls with a history of maltreatment are at heightened risk for health-risking behaviors, including unsafe sexual behaviors and drug use. However, few studies have examined the views of this population in regard to sexual partner choice, sexual behaviors, and decisions to use drugs with sexual partners. Methods We conducted 15 semistructured, open-ended qualitative interviews with young women ages 18-24 with a history of maltreatment and asked them to reflect on their experiences as adolescents. We used the constant comparison method to group the qualitative coded data into themes. Results Analysis of the interviews suggested that adolescent girls with maltreatment histories often report that they chose partners who are promotive of risky drug and sexual behavior. The interviews also provided insight into why this population is likely to use drugs with their partner and why they might be hesitant to talk about or practice safe sex with their partner. Conclusion The young women's feedback highlighted five areas where adolescent girls with maltreatment histories could benefit: (a) provision of information about partner characteristics that are promotive of both risky behavior and those that are linked to healthy relationships, (b) provision of information about how one's partner can influence one's own drug use, (c) practice talking about safe sex with partners, (d) provision of information about safe sex practices and the risks associated with unsafe sex, and (e) provision of information about the risks associated with drug use and unsafe sexual behavior to adolescent boys.